A proposed scoring system for assessing the severity of actinic keratosis on the head: actinic keratosis area and severity index. (3rd May 2017) - Dirschka, T.; Pellacani, G.; Micali, G.; Malvehy, J.; Stratigos, A.J.; Casari, A.; Schmitz, L.; Gupta, G.; ,
Abstract: Background: Actinic keratosis (AK) severity is currently evaluated by subjective assessment of patients. Objectives: To develop and perform an initial pilot validation of a new easy‐to‐use quantitative tool for assessing AK severity on the head. Methods: The actinic keratosis area and severity index (AKASI) for the head was developed based on a review of other severity scoring systems in dermatology, in particular the psoriasis area and severity index (PASI). Initial validation was performed by 13 physicians assessing AK severity in 18 AK patients and two controls using a physician global assessment (PGA) and AKASI. To determine an AKASI score, the head was divided into four regions (scalp, forehead, left/right cheek ear, chin and nose). In each region, the percentage of the area affected by AKs was estimated, and the severities of three clinical signs of AK were assessed: distribution, erythema and thickness. Results: There was a strong correlation between AKASI and PGA scores (Pearson correlation coefficient: 0.86). AKASI was able to discriminate between different PGA categories: mean (SD) AKASI increased from 2.88 (1.18) for 'light' to 5.33 (1.48) for 'moderate', 8.28 (1.89) for 'severe', and 8.73 (3.03) for 'very severe' PGA classification. The coefficient of variation for AKASI scores was low and relatively constant across all PGA categories. Conclusions: Actinic keratosis area and severity index is proposed as a new quantitative tool for assessing AK severity on the head. It may be useful in the future evaluation of new AK treatments in clinical studies and the management of AK in daily practice.